Efficiency enhancement in main path extraction in mRNA vaccine field: A novel approach leveraging intermediate patents, with shielding origin and terminus patent edges - Ting Zhang; Zhongquan Jian; Juan Chen; Dongzi Xu; Xiaoyi Yang; Yan Lu; Shu Yan; Lizi Pan; Qingqiang Wu; Zhaolian Ouyang (Human Vaccines & Immunotherapeutics)
mRNA vaccines offer groundbreaking technological advantages and broad application potential. Their rapid advancement, particularly during the COVID-19 pandemic, is the result of decades of research and numerous technological breakthroughs. These discoveries build upon each other, forming dense, interconnected networks of progress. Studying the technological development paths of mRNA vaccines is therefore essential. Main path analysis (MPA) is particularly effective for mapping out development trajectories within complex and interconnected networks, which serves as a powerful tool for identifying key nodes and innovations. This study introduces a novel approach to extracting main paths from a patent citation network in the mRNA vaccine field. Initially, we shielded edges connecting the origin and terminus patents. Subsequently, we extracted the main paths from intermediate patents, and then, we reintegrated the edges connecting the origin and terminus patents based on the citation relationships, resulting in a comprehensive extraction of the main paths. The research findings indicate a consistency among the global main paths, global key-route main paths, local forward main paths, and local key-route main paths within the mRNA vaccine field. The patents on the main paths predominantly focus on nucleic acid modifications and delivery systems. The local backward main paths identify a greater number of patents, especially those related to litigation, offering a richer and more diverse set of technological insights. This study significantly advances the methodology of MPA, with the innovative shielding technique offering a fresh perspective for navigating complex networks and providing a deeper understanding of technological development in the mRNA vaccine domain.